Dampak Wanprestasi pada Proses Perizinan: Perspektif Hukum dan Kebijakan dengan Tinjauan Pasal 1244 KUHPerdata - Fortuna, Miranda Dewi; Hermawan, Muhammad Bayu (Neolectura, 2025)
This research aims to analyze the impact of default on the licensing process in the context of civil law in Indonesia, especially based on the provisions of Article 1244 of the Civil Code (KUHPerdata). Default, which refers to the failure of a party to fulfill the obligations agreed upon in the agreement, can have a significant impact on the smoothness and validity of the licensing process, both in the punlic and prvate sectors. This research uses a normative-analytical approach to explore how the article regulates the legal consequences arising from default as well as the extent to which these legal provisionis can influence the policy of granting permits by the relevant agencies. The research results show that default can lead to cancellation or delay in granting permits if interested parties do not fulfill the requirements of existing agreements, with far reaching impacts on the stability of oublic administration and the investment cimate. This research also identifies the need to improve licensing policies that take into account aspects of civil law in order to create a balance between legal interests and the need for sustainable development